The Relationships of Expectancy, Instrumentality and Valence for Motivation in Self-Employment: A Mediation of Entrepreneurial Motivation in Nigeria - Adamu, Muhammad; Abdu Shakur, Mahani Mohammad (International Journal of Business and Management Future, 2018)
The aim of this article is to investigate the motivation of potential entrepreneurs toward the realization of a new business creation. Universally, it is evident that the motivation of potential entrepreneur stem from both the individual factors and the environment matched together to trigger entrepreneurial motivation. The Vroom’s Expectancy Motivation Theory explains self-employment in terms of an individual’s motivation and ability to start a business. Businesses are created by those with the motivation and capability to realize it. Based on the Vroom’s expectancy motivation theory (1964), the new business start-up specific expectancy, instrumentality and valence are key components of entrepreneurial motivation and this translates into the efforts, behavior sand performance that would in the end lead to a new business start-up among the potential entrepreneurs. The methodology used in this research was based on a positivist philosophy that entails a deductive approach with a quantitative technique through a cross-sectional survey. The data were collected with a questionnaire as an instrument for the survey. To attain the objectives of this research, the data of this study were analyzed using PLS-SEM Path Algorithms, Bootstrap path coefficients and Sobel test statistics. The statistical significance of relevant path coefficients that are fundamental in measuring self-employment among potential entrepreneurs were assessed and evaluated. The results confirm the supposition that expectancy, instrumentality and valence enhance entrepreneurial motivation for a new business start-up. Furthermore, external factors such as vocational training, machinery/equipment and ICT’s were also significantly found to exert an impact on the potential entrepreneur’s new venture creation.